HUKUM PERKAWINAN DAN KEWARISAN DALAM TATA HUKUM INDIA DAN PAKISTAN - Muhammad Nur Shiddiq (Study Program of Islamic Family Law, Syari'ah Faculty, University of Al-Hikmah Indonesia, 2021)
This paper discusses the reform of Islamic law, especially family law in the Indian and Pakistani legal systems. The merger between India and Pakistan in this paper is based on the historical fact that at first the two countries were a country that was colonized by the British, until finally Pakistan chose to secede, and became a republic with the name of the Islamic Republic of Pakistan. By using a literature study, this paper finds information that India and Pakistan are moderate in carrying out reforms in family law, but not as liberal as some other Muslim countries. The finding of this paper is that, India and Pakistan generaly carry out Islamic family law reforms that are almost the same. This could be because both in the pre-independence period were one country. In addition, because the majority of the population of these two countries adheres to the mazhab Hanafi.